Acoustic performance and modal analysis for the muffler of a four-stroke three-cylinder inline spark ignition engine. (26th August 2021) - Chatterjee, Sushovan
This work presents a concise analytical report on four suggested design modifications (geometrical configuration of the resonating chamber) of a practical muffler model based on acoustic performance and reduction of back pressure. The existing model shows a very low acoustic transmission loss (15.8 dB) with a back pressure of nearly 2.52 × 10 5 Pa. The second proposed model provided better attenuation of 23.2 dB transmission loss but produced more back pressure (2.70 × 10 5 Pa). Modification of the second model by tapering of the inlet pipe's outlet accounted for the reduction in back pressure to around 2.30 × 10 5 Pa and increased the noise attenuation level by 1.2 dB. More significant attenuation of noise (14.8 dB) was observed in the fourth model without any back pressure. The fifth model produced the highest attenuation of 57.1 dB as compared to the other four models with undesirable highest back pressure around 2.83 × 10 5 Pa.